Do The Foreign Workers Need To Speak Indonesian? - I Made Udiana; I Made Sarjana (University of Udayana, 2019)
The foreign workers are one of the important asset supporting business activities in the globalization era. However, an easy requirement for a foreign worker who works in Indonesia such as dropping language requirement tends to decrease local worker opportunity. The aim of this study to elaborate on the impact of cutting language requirement for foreign workers in new Indonesian regulation. This study uses a comparative approach. The study indicates that Article 36 of the Minister of Manpower Regulation Number 16 of 2015 is contrary to the higher legal norm, namely Article 33 of Law Number 24 of 2009. Based on Stufenbau Theory concerning the Act No. 12 of 2011 concerning the Establishment of Law and Regulation, the lower level will be not applicable. Therefore, revision for the Decree of Manpower Regulation is needed to legal certainty and fairly opportunity for local workers.